Game Techniques in Group Guidance to Improve Post-Covid-19 Interpersonal Communication in Students - Katharina Edeltrudis Perada Korohama; Maria Kristina Deo (Universitas Pendidikan Ganesha, 2023)
The problem arising from the Covid-19 pandemic is the need for more interpersonal communication with students and lecturers. Because educational institutions conduct online learning, students need to communicate properly., Services are needed to improve student communication To overcome these problems. This study aimed to analyze the influence of Group Guidance Services Using the Games Method on the Improvement of Interpersonal Communication Post-Covid-19 Pandemic Student Guidance and Counseling. This study uses quantitative and experimental research, namely pre-experimental with a one-group pretest-posttest design. The population in this study amounted to 190 people. The sampling was a purposive sampling method with a final sample size of 12 students. The data collection technique uses a Likert scale questionnaire. The data analysis technique used is descriptive analysis and paired sample t-test further test analysis with the help of the SPSS For Windows 20 Version program. The results showed a significant difference between before and after treatment. It was concluded that group guidance services using the game method effectively improved student interpersonal communication.